Anticipated Impact of In-Car Mobile Calls on the Electromagnetic Interaction of Handset Antenna and Human - Yahya, Salah I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
This paper investigates the impact of the in-car mobile call on the electromagnetic interaction of the mobile handset antenna and user’s head. This impact was evaluated from two different perspectives; First, the antenna performance, e.g., total isotropic sensitivity and total efficiency, and second, the specific absorption rate (SAR) induced in the user's head. A Yee-FDTD based electromagnetic solver was used to simulate a mobile phone in hand close proximity to head at cheek and tilt positions, and working at a frequency of 1900 MHz (GSM 1900/PCS) while making a call inside a car. A Specific Anthropomorphic Mannequin (SAM) was used to simulate the user’s head, a generic phone was used to simulate the mobile phone, a semi-realistic model with three tissues, i.e., skin, bone and muscle, was used to simulate the user’s hand, and a CAD model of Ferrari F430-brand was used to simulate the car. The results showed a considerable degradation in the mobile phone antenna performance while making a mobile phone call inside a car that may drive the mobile phone increases its radiated power to establish a successful connection with the base-station antenna, and consequently increases the induced specific absorption rate in the user’s head.